Improvement of Bread Nutrition With The Addition of Coffee Silverskin as a Source Of Dietary Fiber And Antioxidants - Rizkaprilisa, Windy; Hapsari, Martina Widhi; Paramastuti, Ratih; Pebrianti, Suci Apsari (Food ScienTech Journal, 2023)
Prevention of obesity can be done by reducing the intake of foods high in carbohydrates and fats, then replacing them with high dietary fiber. Silverskin is a by-product of coffee beans with dietary fiber and antioxidants, which can potentially treat obesity. Indonesia has a typical regional bread, "Gandjel Rel" from Semarang, which is box-shaped, brown with a sprinkling of sesame on the surface, and has a cinnamon taste. This study aimed to increase the functional properties of "Gandjel Rel" bread through the nutrification of silverskin to enrich the content of dietary fiber and antioxidant compounds so it can be used to treat obesity. The main ingredient in this research is silverskin from Robusta coffee. In making bread, silverskin flour is added with a variation of 0; 1; 2,5; and 5%. The bread was analyzed about dietary fiber, antioxidant activity, physical and chemical properties. The bread was subjected to sensory analysis using 20 untrained panelists to assess the acceptability of the given bread samples. Bread with silverskin has higher dietary fiber (3,33-7,18% insoluble fiber and 0,25-0,77% soluble fiber) and antioxidant activity (26,23-31,36%). Silverskin did not change the texture of the bread and made darker and yellowish color. The panelists preferred bread by adding 1% silverskin with a nutritional content of 11,33% protein, 17,40% fat, and 66,42% carbohydrates. This bread has the potential as a functional food that is useful in treating obesity.